Linking determinants of innovation speed to innovation performance among employees of manufacturing industry in Malaysia / Mohd Rizaimy Shaharudin ... [et al.] - Shaharudin, Mohd Rizaimy; Mohd Hussain, Siti Hajar; Azman, Azlin; Mohamad Yunus, Fauziah; Mokhtar, Suhaibah (2019)
Greater innovation is necessary for the industry to move up in the global value chain. Company performance is boosted by the firm's ability to increase innovation to meet the increasingly competitive level and the reduction of the product life cycle. Nevertheless, a local newspaper The Star Online on 21 October 2016 reported that despite the importance of innovation improvement in industrial production, however, the innovation in Malaysia is still sluggish due to lack of funding, limited support from the private sector in R&D and scarcity of the researchers. Also, the New Straits Times reported on 15 October 2018 that new businesses in the country are not innovating. The new companies only introduced about 16 per cent of new products in the last seven years.